Influence of acute selective endothelin-receptor-A blockade on renal hemodynamics in a rat model of chronic allograft rejection - Knoll, Thomas; Oltersdorf, Jens; Göttmann, Uwe; Schaub, Meike; Michel, Maurice Stephan; Kirchengast, Michael; Woude, Fokko J. van der; Rohmeiss, Peter; Braun, Claude (Transplant international, 2003)
We have recently demonstrated up-regulation of renal endothelin (ET) synthesis in a rat model of chronic renal allograft rejection. Treatment with a selective ET-A receptor antagonist improved survival and reduced functional and morphological kidney damage. However, the underlying mechanisms have not yet been elucidated, as ET exhibits both hemodynamic and inflammatory properties. Therefore, in the present study we investigated acute hemodynamic effects of the selective ET-A receptor antagonist LU 302146 (LU) on chronic renal allograft rejection in rats. Experiments were performed in the Fisher-to-Lewis model of chronic renal allograft rejection. Lewis-to-Lewis isografts served as controls. After 2, 12, and 24 weeks, hemodynamic measurements were performed on anesthetized animals. Measurement of mean arterial pressure (MAP) was performed via a catheter in the femoral artery. Renal blood flow (RBF) was measured by an ultrasonic flow probe placed around the renal transplant artery. Medulla blood flow (MBF) and cortex blood flow (CBF) were determined with laser Doppler probes. Hemodynamic response upon intravenous bolus injection of LU (50 mg/kg) was investigated. The application of LU was followed by a decline in MAP that reached statistical significance only in isografts (ISOs) after 12 weeks and allografts (ALLOs) after 24 weeks. RBF slightly decreased in all groups; however, without reaching statistical significance. MBF showed a small increase in ALLO12 and ALLO24 whereas CBF slightly decreased in all groups. Acute ET-A receptor blockade does not induce important hemodynamic effects in kidneys undergoing chronic rejection. The lack of response to ET-A receptor blockade suggests that the beneficial effect of ET receptor antagonists in this model is likely to be due to improvement of renal morphology.
Gesehen am 04.07.2022